Teorija rasti kovinskih oksidnih plasti - Cvelbar, Uroš (Vakuumist, 2002)
The article deals with growth of metal oxides and general oxidation theory. According to the theory there are three types: linear, logarithmic and parabolic. The idela case is the parabolic growth, were the growing oxide layer is compact without any micro- and macrocracks and thicker than 10 nm. This growth model can be easily described by diffusion that explains also the Wagner oxidation model. A more sophisticated model includes also the temperature dependence. Similar results for parabolic growth come from the diffusion on grain boundaries. Results of linear or logarithimc growth are presented, but the real case is actually the combination of all three models, depending on different parameters. The oxidation is very useful in modern industry that is why some new examples are presented.
Keywords: oksidne plasti; rast; oksidacija; modeli; tanke plasti; kovine